2005
DOI: 10.1103/physrevlett.94.233401
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Size Dependence in the Melting Temperatures of Free Sodium Clusters: An Explanation for the Calorimetry Experiments

Abstract: The meltinglike transition in unsupported Na N clusters (N 55, 92, 147, 181, 189, 215, 249, 271, 281 and 299) is studied by first-principles isokinetic molecular dynamics simulations. The irregular size dependence of the melting temperatures T m observed in the calorimetry experiments of Schmidt et al.[Nature (London) 393, 238 (1998)] is quantitatively reproduced. We demonstrate that structural effects alone can explain all broad features of experimental observations. Specifically, maxima in T m N correlate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 36 publications
2
60
0
Order By: Relevance
“…This conclusion supports the existence of a relationship between the N dependence of v(N )/v(2) as evaluated by us and that of the T m observed by Habarland et al Further, the more precise DFT-LDA molecular dynamics calculations predict that T m of Na 40 is higher than that of Na 55 41 . T m of Na 40 has not yet been observed experimentally. Our calculation results of v(N )/v(2) do not contradict with the result of the DFT-LDA molecular dynamics study 41 with regard to the relationship between Na 40 , and Na 55 .…”
Section: N Dependence Of the Averaged Atomic Densitymentioning
confidence: 96%
See 2 more Smart Citations
“…This conclusion supports the existence of a relationship between the N dependence of v(N )/v(2) as evaluated by us and that of the T m observed by Habarland et al Further, the more precise DFT-LDA molecular dynamics calculations predict that T m of Na 40 is higher than that of Na 55 41 . T m of Na 40 has not yet been observed experimentally. Our calculation results of v(N )/v(2) do not contradict with the result of the DFT-LDA molecular dynamics study 41 with regard to the relationship between Na 40 , and Na 55 .…”
Section: N Dependence Of the Averaged Atomic Densitymentioning
confidence: 96%
“…If the conclusion about the relation between the cluster v(N ) or v(N )/v(2) and T m in Na N holds for Cu N and Ag N for N ≤ 55, it is expected that T m of Cu 40 and Ag 40 are lower than that of Cu 55 and Ag 55 , respectively. For N ≤ 22, the volume of the most stable cluster changes significantly with the structural type transitions (L→ P→ O→ C) described in section III.…”
Section: N Dependence Of the Averaged Atomic Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…This differs from the related case of sodium clusters, where purely geometrical arguments explain the size dependence of the latent heats. 8,11,24,25 We have previously shown 18 for sodium clusters with around 147 atoms that the solid cohesive energies show a marked maximum at the geometrical shell closing but not at the nearby electronic shell closing. Therefore, the correlation between latent heats and solid cohesive energies holds also for sodium clusters with around 147 atoms, although it has a different ͑purely structural͒ origin.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it appears that the features observed in the melting temperatures and latent heats for sodium clusters can be explained by geometric shell closings for icosahedral packing. 8,24,25 We recently showed that the latent heats for melting are correlated with the solid cluster cohesive energies. 18 Maxima in the latent heats occur for clusters that are particularly strongly bound.…”
Section: Introductionmentioning
confidence: 99%